2015
DOI: 10.1016/j.autcon.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimal control of an energy-efficient hybrid solar air conditioning system

Abstract: The paper addresses the modeling and optimal control problem of a new hybrid solar-assisted air conditioning system developed for performance enhancement and energy efficiency improvement. To regulate the mass flow rate of the refrigerant vapor passing through a water storage tank for increasing the refrigerant's subcooling process at partial loads, we propose a new discharge bypass line together with an inline solenoid valve, installed after the compressor. In addition, to control the air flow rate, a variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In 2016, Guo et al [88] presented the optimal ratio of turbine pressure drop to the available total pressure difference and examined it broadly using theoretical analysis and 3D numerical simulations, for solar chimney power plant (SCPP). In 2015, Ha and Vakiloroaya [129] addressed the modelling and control problem of a fully developed hybrid solar-assisted, splitsystem air-conditioner to improve the performance of an existing solar air-conditioning system. In 2013, LizarragaGarcia et al [130] presented an optimization case study for the time-variable operation of the concentrated solar power on demand (CSPonD) solar energy receiver and thermal energy storage.…”
Section: 2mentioning
confidence: 99%
“…In 2016, Guo et al [88] presented the optimal ratio of turbine pressure drop to the available total pressure difference and examined it broadly using theoretical analysis and 3D numerical simulations, for solar chimney power plant (SCPP). In 2015, Ha and Vakiloroaya [129] addressed the modelling and control problem of a fully developed hybrid solar-assisted, splitsystem air-conditioner to improve the performance of an existing solar air-conditioning system. In 2013, LizarragaGarcia et al [130] presented an optimization case study for the time-variable operation of the concentrated solar power on demand (CSPonD) solar energy receiver and thermal energy storage.…”
Section: 2mentioning
confidence: 99%
“…More specifically, ESP-r and Fluent tools were used for simulating heat transfer and fluid dynamics, respectively. Again, an ad-hoc numerical algorithm was implemented in TRYNSIS in order to predict the energy performance of a hybrid solar air conditioning system under transient loads (Ha and Vakiloroaya (2015)). In the same TRYNSIS software platform two hybrid micro-generation systems in a load sharing application among residential and office buildings were successfully modeled by Canelli et al (2015).…”
Section: Simulation Of Integrated Systemsmentioning
confidence: 99%
“…At steady-state conditions, the compressor power consumption was decreased from 1.45 to 1.24 kW, which is traduced by a global energy saving of about 14 and 7.1% for only the compressor. Likewise, an energy saving achieved by the condenser fan is about 2.6% [25], which allows increasing the COP. Hence, the authors reported that the system is able to satisfy efficiently the cooling requirements.…”
mentioning
confidence: 99%
“…On the other hand, the investigation [25] couples the solar energy to a traditional vapor compression air conditioner to perform a new hybrid solar-driven AC system. The proposed system was modeled and controlled using TRNSYS software in order to improve its energy efficiency.…”
mentioning
confidence: 99%